Socio-Demographics Correlate of COVID-19 Vaccine Hesitancy During the Second Wave of COVID-19 Pandemic: A Cross-Sectional Web-Based Survey in Saudi Arabia - AL-Mohaithef, Mohammed; Padhi, Bijaya Kumar; Ennaceur, Soukaina (Frontiers in Public Health, 2021)
Background: The Coronavirus disease 2019 (COVID-19) pandemic is considered a major global public health threat affecting across the life course and socioeconomic aspects of life. Globally acceptance to an effective vaccine is the most anticipated resolution. This study aims to evaluate intent to be vaccinated among public in Saudi Arabia during the second wave of COVID-19 pandemic. Methods: A cross-sectional web-based study was designed in Saudi Arabia. Study participants (N=658) were recruited through snowball sampling. SurveyMonkey platform was used to record the response. Cross-tabulation were performed by participants’ intention to vaccinate against COVID-19 virus with sociodemographic characteristics and respondents’ risk perception towards COVID-19, trust in the healthcare system, and their history of vaccine hesitancy behavior. Multivariable logistic regression analysis was performed to compute the predictors of vaccination intention among the study participants. Results: 658 participants were completed the survey (females = 47.4%). Of the 658 participants 351 (53.3%) have shown intent to be vaccinated. 519 (78.8%) of the participants were reported to be at high risk of COVID-19, and 307 (46.6%) were reported to trust the healthcare system in the country. The multivariable analysis shows respondents with a high-risk perception (OR: 2.27, 95% CI: 1.49-3.48); higher trust in the healthcare system (OR: 3.24, 95% CI: 2.32-4.61) was found to be the significant factor affecting the decision in acceptance of the COVID-19 vaccine in Saudi Arabia. Conclusion: Participants reported high knowledge towards COVID-19 virus, and vaccine developments. About half (46.6%) of the study participant reported refusal/hesitancy towards the vaccine during the second wave of the pandemic in Saudi Arabia. The study highlighted that higher risk perception and higher trust in the healthcare system were found to be the main reasons for participants' intentions behind the vaccination.